The smart set - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Progress is being made in the development of the Toolkit for managers of information projects, following a meeting of some 30 experts in evaluation and information management in Amsterdam, The Netherlands in late November 2002. Organised by its host...